The xeroderma pigmentosum group B protein ERCC3 produced in the baculovirus system exhibits DNA helicase activity. - Ma, L (1994)
The XPB/ERCC3 gene corrects the nucleotide excision-repair defect in the human hereditary disease xeroderma pigmentosum group B and encodes the largest subunit of the basal transcription factor BTF2/TFIIH. The primary sequence of the XPB/ERCC3 protein features the hallmarks of seven helicase motifs found in many known and putative helicases or helicase-related proteins. Recently, the multiprotein BTF2/TFIIH complex has been found to be associated with DNA helicase activity. To explore the properties and functions of XPB/ERCC3, we have used the baculovirus/insect-cell expression system to produce recombinant protein. We report here the construction and analysis of recombinant baculovirus expressing XPB/ERCC3. The XPB/ERCC3 protein is synthesized at a relatively high level in baculovirus-infected insect cells. While the majority of XPB/ERCC3 end up in the insoluble fraction of insect cell lysates, a minor fraction of recombinant protein is present in soluble form which can be purified under native conditions. We have found that a DNA helicase activity is associated with the purified XPB/ERCC3 protein, suggesting that XPB/ERCC3 may function as a DNA helicase in local unwinding of DNA template both in the context of transcription and nucleotide excision repair.